Perceived Clinical Competence among Undergraduate Nursing Students in the University of Gondar and Bahir Dar University, Northwest Ethiopia: A Cross-Sectional Institution Based Study. (23rd May 2016) - Bifftu, Berhanu Boru; Dachew, Berihun Assefa; Tadesse Tiruneh, Bewket; Mekonnen Kelkay, Mengistu; Bayu, Netsanet Habte
Abstract : Introduction . To produce competent, confident, critical thinker with the ability to lead, to question, and to be questioned is needed in nursing education. This study aimed to assess perceived clinical competence among nursing students. Methods . This cross-sectional study was conducted in two nursing schools in Ethiopia. Data were collected using pretested, semistructured questionnaire. Clinical competence was measured by Short Nursing Competence Questionnaires. Binary logistic regression model was fitted to identify associated factors. An adjusted odds ratio with 95% confidence interval was computed. Results . Overall, 48.7 % of the participants perceived themselves as clinically competent. Social support [moderate (AOR = 5.87, CI: 1.346, 9.586), high (AOR = 6.27, CI: 1.741, 7.608)], type of institution [(AOR = 3.20, CI: 1.331, 7.694)], year of study [(AOR = 1.89 (4.760, 18.510)], attending theoretical classes [(AOR = 0.83 CI: 0.017, 0.412)], and clinical environment [poor (AOR = 5.65, CI: 1.837, 13.453), fair (AOR = 7.31, CI: 2.790, 15.356), good (AOR = 9.31, CI: 3.260, 19.967)] were associated with clinical competence. Conclusion . More than half of the study participants perceived themselves as incompetent. Social support, type of institution, year of study, attending theory classes, and clinical environment were associated with perceived clinical competence. Authors suggested that nursing students attend their theoretical class and utilize the available resource.